Parent and Peer Influence on Recreational Use of Pain Medication: Are Their Influences Similar to That of Marijuana Use?. (28th August 2013) - Fleary, Sasha; Taylor, Aaron; Heffer, Robert W.; McKyer, E. Lisako
Abstract : Parent and peer disapproval were examined as potential predictors of recreational use of over-the-counter (OTC) and prescription pain medication. Risk perception was studied as a potential mediator of the effects of parent and peer disapproval. Four hundred and sixty-five college students (M age = 18.57, SD = 0.86 ) were recruited between September 2009 and September 2010. Participants completed an online survey about their recreational medication use, other substance use, and correlates of use. Path analyses showed that predictors of OTC and prescription pain medication recreational use are largely similar to predictors of marijuana use in college students such that risk perception mediated both the effect of parent and peer disapproval on dichotomous misuse, and peer disapproval had a significant direct effect on dichotomous misuse. Prevention interventions for recreational use of pain medication should target risk perception and peer disapproval.